2013
DOI: 10.1097/fpc.0b013e3283649b9a
|View full text |Cite
|
Sign up to set email alerts
|

Utility of integrated pharmacogenomic testing to support the treatment of major depressive disorder in a psychiatric outpatient setting

Abstract: These findings replicate previous studies and demonstrate significantly improved depression outcomes with use of GeneSight, an integrated, multigenetic pharmacogenomic testing platform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
173
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(177 citation statements)
references
References 15 publications
3
173
1
Order By: Relevance
“…Their findings demonstrated that use of the test would lead to improved outcomes with antidepressant medication. The guided group experienced greater improvement in three depression scores from baseline on the HAMD, QIDS, and PHQ, when compared to the unguided group (153).…”
Section: Dmetmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings demonstrated that use of the test would lead to improved outcomes with antidepressant medication. The guided group experienced greater improvement in three depression scores from baseline on the HAMD, QIDS, and PHQ, when compared to the unguided group (153).…”
Section: Dmetmentioning
confidence: 99%
“…children and geriatric populations); address potential gender effects; and consider variations due to ethnicity. In addition, further studies comparing pharmacogenetic-guided treatment versus treatment as usual (TAU) are required, such as the study on antidepressants published by Hall-Flavin et al (153).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of earlier study designs examined a narrow objective, such as looking at only the relationship between a single gene variant of a single gene and a single outcome measure. It has been demonstrated that considering all relevant genes for a particular drug when using pharmacogenetically-guided drug selection, also known as combinatorial pharmacogenetics, results in better outcomes than when compared to either no pharmacogenetic guidance or single gene/single drug-based pharmacogenetic guidance [8,9]. It is reasonable to expect that adoption of combinatorial pharmacogenetic approaches in clinical practice will continue to show superior clinical benefit and become best practice in pharmacogenetic testing.…”
Section: Editorialmentioning
confidence: 99%
“…It has been demonstrated that considering all relevant genes for a particular drug when using pharmacogenetically-guided drug selection, also known as combinatorial pharmacogenetics, results in better outcomes than when compared to either no pharmacogenetic guidance or single gene/single drug-based pharmacogenetic guidance. 8,9 It is reasonable to expect that adoption of combinatorial pharmacogenetic approaches in clinical practice will continue to show superior clinical benefit and become best practice in pharmacogenetic testing.…”
Section: Editorialmentioning
confidence: 99%